PERANAN PEMERINTAH DAERAH DALAM PEMBERDAYAAN PETANI PALA DI KABUPATEN FAKFAK - Albertus Dogopia (Prima Center Indonesia, 2017)
As for the aspects of the study related to the government's role in the empowerment of farmers nutmeg in Fakfak includes six aspects of how to understand the aspirations of the people, how to build popular participation, prepare the community with better, open a dialogue with the community, open lines of information and necessary access, creating regulatory instruments and a mechanism for setting the qualitative assessment method with survey-descriptive approach. Collecting data through interviews, documentation and observation techniques and analysis menhubungkan third test data by categories defined by the existing theories. The results showed that the role of local government to the six aspects Fakfak is not maximized in empowering farmers nutmeg. This condition is measured from the unfulfilled aspects of the study based on the analysis. As a recommendation, the local government Fakfak need to improve these aspects to be able to empower farmers in Fakfak nutmeg, mace so that commodities can actually be a source of income in improving the socio-economic life of farmers and could contribute Fakfak PAD.Keywords: Empowerment; Farmers